Perception of Nurses and Relatives on Family Needs of Critically Ill Patients: A Hospital Based Comparative Study - Pandey, Sabita; Shrestha, Roshanee; Paudel, Narayani (Journal of Karnali Academy of Health Sciences, 2020)
Background: Critical ill patients are not able to decide about their treatment and their relatives usually asked for the treatment decisions on behalf of the patient. At the time of critical illness, all family members or relatives experience crises and may be exhausted. Recognizing and addressing the relative’s needs is a very important aspect of holistic health care to critically ill patients.Methods: A descriptive cross-sectional study was conducted to make a comparison between the nurses’ and relatives’ perceptions regarding the needs of critically ill patients’ family members’ in the Nepalese context. A convenient sample of 50 nurses and 50 relatives who meet the inclusion criteria were selected and interviewed by using a structured questionnaire in the different intensive care units of Kathmandu Medical College and Teaching Hospital, Kathmandu, Nepal during the period of January to April 2018. The data were analyzed by using descriptive and inferential statistics in the statistical package for social sciences version 16.Results: The majority, (86%) of the relatives ranked “to know specific facts concerning the patient’s progress and treatment” as the topmost very important need, and 80% of the nurses’ ranked this need as a very important need. The majority of nurses (86%) ranked “to receive explanations about the environment of critical care unit for the first time” as a topmost very important need, whereas, only 54% of the relatives had ranked this need as very important to them. There was a statically significant positive correlation among some need statements between the two groups.Conclusion: There was a significant difference in the perception of some aspects of family needs by the nurses and relatives. Nurses’ mean score was lower than the relatives’ which can be a major source of disputes among nurses and relatives in the intensive care units.Keywords: Intensive Care Unit, critically ill patient, family needs, nurses’ perception and relatives, perception